Do I Really Know You? Do You Really Know Me? Empathy Amid Diversity in Differing Learning Contexts. (February 2016) - Kasl, Elizabeth; Yorks, Lyle
We explore the need for empathy in diverse groups, conceptualize the epistemology of empathy in relationship to whole-person dialogue, and examine strategies for creating empathic space that take into consideration the paradox of diversity . Two examples from our practice illustrate the role of empathic connection in personal learning and organizational change.